SYNTHESIS OF MAGNETITE-FILLED NANOCOMPOSITE AS ELECTROMAGNETIC WAVE ABSORBING MATERIALS AT X- AND KUBAND FREQUENCY - ADEBAYO, LAWAL LANRE (2020)
To tackle the issue of electromagnetic (EM) pollution and EM interference, fabrication of advanced, novel and superior microwave absorbing materials (MAM) with high EM wave absorption, wide absorption bandwidth, lightweight and cost-efficient have received huge attention. To date, magnetite (Fe3O4) is being thoroughly investigated as MAM, due to its exceptional dual EM properties (permittivity and permeability), and proper saturation magnetization. However, large density and impedance mismatch are some of the limiting factors that hinder its EM wave absorption performance (EMAP). Hence, with the expectation of an efficient microwave absorbing materials, the aim of this research is to prepare Fe3O4-filled composites as enhanced MAM. Fe3O4 nanoparticles were prepared by a facile sol-gel method. Citric acid-coated Fe3O4 nanocomposites were prepared by coprecipitation method. Three-dimensional carboncoated Fe3O4 composites (3DC@Fe3O4) were prepared by hydrothermal method. Several characterization techniques were used to study the physiochemical properties of the samples and the results were analyzed and presented. The EMAP of all samples were studied at X-band (8.2-12.4 GHz) and Ku-band (12.4-18.0 GHz) Frequency range. The 3DC@Fe3O4 composites display and enhanced EMAP with a minimum RL value of -46.4 dB at 16.85 GHz with 2.0 mm absorber thickness. These good EMAP could be attributed to structural advantages as well as favorable impedance matches derived from the synergistic effect of proper dielectric loss from carbon microspheres and magnetic loss contribution from Fe3O4 nanoparticles.